IMPLEMENTING THREE STEPS INTERVIEW TECHNIQUE IN TEACHING LEARNING SPEAKING ACTIVITY - Prasetyo, Reno (UNIVERSITAS SLAMET RIYADI, 2017)
AbstractIn Indonesia, English is a foreign language. English should be learnt by the students in every levels education in this country. No wonder, speaking is one of language skills that should be mastered by students especially in globalization era. However, several foreign language learners face some difficulites in learning speaking. This study was to answer the problem and to show the improvement after the implementation of Three Steps Interview technique in teaching learning process at eleventh grade students of SMAN 6 Surakarta in 2017/2018 academic year. The method of the study was classroom action research which was conducted from January until February 2018. To collect the data, test (oral test) and non-test (interview, observation, and documentation) techniques were employed. Meanwhile, t-test was used to analyze the data . The result of the study proved that Three Steps Interview technique gave significant improvement to the students’ speaking skill. It was seen from the result of the mean score of post-test 2 was 74.41 better than 64.14 in post-test 1 and the 47.71 in pre-test. Meanwhile, the result of analyzing the t-test between pre-test and post-test 1 were 15.06 and post-test 1 and post-test 2 were 11.87. Based on the fact above, it can be conclude that Three Steps Interview technique was one of alternative technique to improve students’ speaking skill in teaching and learning process. Not only showed the improvement trough the data, but also it made the class condition more conducive and built the student’s cooperation together during teaching learning process. Keywords: Speaking skill, Action Research, Three Steps Interview. AbstrakDi Indonesia, bahasa Inggris adalah bahasa asing. Bahasa Inggris harus dipelajari oleh siswa di setiap tingkat pendidikan di negara ini. Tidak heran, berbicara adalah salah satu keterampilan bahasa yang harus dikuasai oleh siswa terutama di era globalisasi. Namun, beberapa pelajar bahasa asing menghadapi beberapa kesulitan dalam belajar berbicara. Penelitian ini adalah untuk menjawab masalah dan untuk menunjukkan peningkatan setelah penerapan teknik Three Steps Interview dalam proses belajar mengajar pada siswa kelas XI SMAN 6 Surakarta di 2017/2018 tahun akademik. Metode penelitian ini adalah penelitian tindakan kelas yang dilakukan dari Januari hingga Februari 2018. Untuk mengumpulkan data, tes (tes lisan) dan teknik non-tes (wawancara, observasi, dan dokumentasi) dipekerjakan. Sementara itu, uji-t digunakan untuk menganalisis data. Hasil penelitian membuktikan bahwa teknik Wawancara Tiga Langkah memberikan peningkatan yang signifikan terhadap keterampilan berbicara siswa. Itu terlihat dari hasil nilai rata-rata post-test 2 yaitu 74,41 lebih baik dari 64,14 pada post-test 1 dan 47,71 pada pre-test. Sementara itu, hasil analisis uji-t antara pre-test dan post-test 1 adalah 15,06 dan post-test 1 dan post-test 2 adalah 11,87. Berdasarkan fakta di atas, dapat disimpulkan bahwa teknik Wawancara Tiga Langkah adalah salah satu teknik alternatif untuk meningkatkan keterampilan berbicara siswa dalam proses belajar mengajar. Tidak hanya menunjukkan peningkatan melalui data, tetapi juga membuat kondisi kelas lebih kondusif dan membangun kerja sama siswa bersama selama proses belajar mengajar. Kata kunci: Keterampilan Berbicara, Penelitian Tindakan, Wawancara Tiga Langkah